Influence of different formulations and granulation techniques on dissolution of folic acid in film coated tablets - Ljiljana Krsteska; Dejan Kostovski; Ksenija Brzilova; Suzan M.Sejfulah; Sonja Ugarkovic (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2011)
The vitamin folic acid has received considerable attention because of it's role in decreasing risk of neural tube birth defects, and it's potential role in reducing risks of cardiovascular and psychiatric diseases. We evaluated compositions of 5 different formulations in terms of meeting the USP standard for dissolution and disintegration .However all the examined formulations had met the disintegration test but only 3 formulations had met the dissolution requirements to release 75 % of the active ingredient in 45 minutes. The maximum value of dissolution of 97.52 % in S5 composition was achieved by combination of certain excipients (combination of hydrophilic and hydrophobic filler and suitable wetting agent) and wet high shear mixing granulation technique, resulting with optimize release of the active substance.